The Efficacy of Fractional CO2 Laser in the Treatment of Genitourinary Syndrome of Menopause: A Large Prospective Observational Study - Violante Di Donato; Ottavia D'Oria; Andrea Giannini; Maria Scudo; Carmel Sher; Margherita Fischetti; Giorgia Perniola; Innocenza Palaia; Marco Monti; Ludovico Muzii; Pierluigi Benedetti Panici (Clinical and Experimental Obstetrics & Gynecology)
Background: Genitourinary syndrome of menopause (GSM) majorly caused by the physiological decline in estrogen, affects up to 90% of menopausal women. Hormonal therapy seems to be an effective treatment, often not executable for contraindication or patient’s low compliance to local or systemic medical therapy. Fractional CO2 laser therapy is an emerging and effective choice for women affected by vulvo-vaginal atrophy (VVA), promoting collagen regeneration and improving blood flow of the vaginal mucosa and elasticity of tissues. Methods: Ninety-two menopausal Patients affected by vulvo-vaginal atrophy (VVA) were considered for the present prospective observational study. All women were treated with Fractional CO2 laser Lumenis AcuPulse in a fractionated sequential mode laser pulse. Patients were requested to complete questionnaires regarding the Female Sexual Functional Index (FSFI), Female Sexual Distress Scale (FSDS) and severity of Most Bothersome Symptoms (MBS) at baseline (T0) and at three-month following three-treatment-sessions (T1). Results: Data indicated a significant improvement of MBS (vaginal itching (p < 0.0001), post-coital vaginal bleeding (p < 0.002), vaginal dryness (p < 0.0001), dyspareunia (p < 0.0001) and dysuria (p < 0.0001), higher Vaginal Health Index Score (VHIS) (4.1 ± 1.21; 95% CI = 3.84–4.35) and reduces pH (–0.53 ± 0.24; 95% CI = 0.48–0.58) after CO2 laser treatment. A significantly improvement of FSFI Total score (p < 0.0001) and FSDS (p < 0.0001) have been demonstrated. Conclusions: Fractional CO2 laser improves vaginal health as well as signs and symptoms associated with GSM, while significantly elevating quality of life and sexual functionality among postmenopausal symptomatic women.